Anti-windup controller design for singularly perturbed systems subject to actuator saturation - Yang, Chunyu; Zhang, Lingli; Sun, Jing (IET control theory & applications, 2016)
This study considers the problem of anti-windup (AW) controller design for singularly perturbed systems with actuator saturation. The AW controller consists of a dynamic state feedback (DSF) controller and an AW compensator. A convex optimisation problem in terms of linear matrix inequalities is formulated to simultaneously design both the DSF controller and the AW compensator. The resulting AW controller depends on the singular perturbation parameter ɛ and is shown to be well-conditioned for any ɛ of interest. Furthermore, a two-stage design method is proposed to handle the case that ɛ is unknown. An ɛ-independent DSF controller is designed at the first stage, and then an ɛ-independent AW compensator is constructed by solving a convex optimisation problem. Both of the methods can achieve a desired stability bound and enlarge the basin of attraction at the same time. Finally, examples are given to show the advantages and effectiveness of the obtained results.